2017
DOI: 10.1097/gox.0000000000001550
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Analysis of Cutaneous Perforator Distribution in the Forearm

Abstract: Background:Few reports describe the distribution of cutaneous perforators from the radial and ulnar arteries in the forearm. This study aimed to map the location of the cutaneous perforators that arise directly from the radial and ulnar arteries in cadavers.Methods:Twenty-nine human cadaveric forearms were dissected. All radial and ulnar arteries cutaneous perforators were analyzed for total number and distribution. To define the distribution of each cutaneous perforator, the forearm was divided into 10 sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…As reported by Inoue and Taylor, 10 it is safer to include perforators from a radial and ulnar recurrent artery to stabilize blood flow near the cubital fossa. To do so, we included superficial flexor muscles to the flap, and it is possible to easily incorporate musculocutaneous perforators of ulnar and radial arteries 10–13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by Inoue and Taylor, 10 it is safer to include perforators from a radial and ulnar recurrent artery to stabilize blood flow near the cubital fossa. To do so, we included superficial flexor muscles to the flap, and it is possible to easily incorporate musculocutaneous perforators of ulnar and radial arteries 10–13 …”
Section: Discussionmentioning
confidence: 99%
“…To do so, we included superficial flexor muscles to the flap, and it is possible to easily incorporate musculocutaneous perforators of ulnar and radial arteries. [10][11][12][13] Some have also suggested that the postoperative contour of the shoulder is better to fit a prosthesis if the flap has a volume of flexor muscle groups. 2,14 Concerning the size of the flap that can be harvested, Kimura et al 11 reported that the average length of the forearm from the volar aspect of the pisiform bone to the medial epicondyle of the humerus was 22.8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…3 Their findings have been supported by other studies that found that ulnar cutaneous perforators are densely represented in an area located between the middle and the proximal one-third of the forearm. 5,6,16,26 Known that in this work, we focused the area of interest in the proximal one-third of the forearm for two main reasons. The first one relates to the fact that we wanted to further investigate the presence of perforators directed to the skin originating from ulnar recurrent arteries, which are located in this area.…”
Section: Discussionmentioning
confidence: 99%
“…An in-depth description on correct program selection and device settings regarding perforator mapping and characterization for microsurgeons has been described by Kehrer et al 18,19 In our study, the analysis for UAPs using US was performed between the pisiform and 100 mm proximal to the pisiform, which was the distal half in the volar forearm. To compare with previous reports, the location of UAP was mapped as described by the previous reports [20][21][22][23][24][25] (►Fig. 5).…”
Section: Discussionmentioning
confidence: 99%